Deteksi Dini Kanker Serviks dan Edukasi Kegunaan Pemeriksaan Pap Smear - Nana Liana; Nurwiyeni; Meta Zulyati Oktora; Anandia Putriyuni (CV. Multi Kreasi Media, 2023)
Cervical cancer is the second largest malignancy after breast cancer in Indonesia. The incidence is increasing every year. In the United States and several other countries, the incidence of cervical cancer has decreased due to public health services and lifestyle changes as well as early implementation through pap smears. In developing countries, the mortality and incidence of cervical cancer has also decreased by 34-80% in the last 50 years. This is sufficient because the period of occurrence of cervical cancer is long and 90-95% of pathological changes in the epithelium can be determined through the Pap smear test. However, in developing countries, health services are still limited and there are no screening programs, cervical cancer is still the leading cause of death in women. Cervical cancer is often diagnosed at an advanced stage and the survival rate is low. On the other hand, the cure rate for early cervical cancer is very high. Therefore, it is important for women to undergo regular pap smears test so that the health condition of the cervix can be monitored and cervical cancer can be detected early.